Experimental Weaving and Twining with Ceramic Crescents from the Late Neolithic and Chalcolithic in Southwestern Iberia - Victoria Priola (EXARC Journal)
Ceramic crescents are a common find at Late Neolithic and Chalcolithic sites in southwestern Iberia (late fourth – third millennium BC). These objects, which often weigh less than 100 g and are perforated on each end, are typically referred to as loom weights and thought to be associated with textile production, although their function remains uncertain. A variety of possible uses have been suggested for similar crescents from other archaeological contexts in Central and Southern Europe and Mesoamerica, including the use of these objects in vertical band weaving, warp twining, and warp-weighted weaving. This experimental project tests the efficacy of these Iberian crescents in each of these methods and compares the results to surviving textile fragments found in southern Iberia contemporary with these tools. My findings suggest that Iberian ceramic crescents could have functioned as warp twining tools or as loom weights with linen threads on a vertical loom.